The end of a monolith: Deconstructing the Cnn-Polo interaction. Issue 2 (2nd April 2016) - Eisman, Robert C.; Phelps, Melissa A. S.; Kaufman, Thomas C.
ABSTRACT: In Drosophila melanogaster a functional pericentriolar matrix (PCM) at mitotic centrosomes requires Centrosomin-Long Form (Cnn-LF) proteins. Moreover, tissue culture cells have shown that the centrosomal localization of both Cnn-LF and Polo kinase are co-dependent, suggesting a direct interaction. Our recent study found Cnn potentially binds to and is phosphorylated by Polo kinase at 2 residues encoded by Exon1A, the initiating exon of a subset of Cnn isoforms. These interactions are required for the centrosomal localization of Cnn-LF in syncytial embryos and a mutation of either phosphorylation site is sufficient to block localization of both mutant and wild-type Cnn when they are co-expressed. Immunoprecipitation experiments show that Cnn-LF interacts directly with mitotically activated Polo kinase and requires the 2 phosphorylation sites in Exon1A. These IP experiments also show that Cnn-LF proteins form multimers. Depending on the stoichiometry between functional and mutant peptides, heteromultimers exhibit dominant negative or positive trans -complementation (rescue) effects on mitosis. Additionally, following the completion of meiosis, Cnn-Short Form (Cnn-SF) proteins are required for polar body formation in embryos, a process previously shown to require Polo kinase. These findings, when combined with previous work, clearly demonstrate the complexity of cnn and show that a view of cnn as encoding a single peptide is too simplistic.